Age- and gender-related characteristics of astigmatism in a myopic population - Yang, Shan; Jiang, Yang; Cui, Ge; Li, Ying (Frontiers in Medicine, 2022)
Purpose: To explore age- and gender-related differences of refractive and corneal astigmatism in myopic patients looking for refractive surgery. Design: A retrospective cross-sectional study. Methods: The medical files of candidates looking for corneal refractive surgery between 2019 and 2021 were reviewed, demographic and refractive parameters including age, gender, refractive status and corneal parameters were analyzed. Results: A total of 1417 eyes of 1417 patients were included. Males had thicker cornea than females, while females had steeper cornea than males, there was no gender-related difference in refractive and corneal astigmatism depending on patients' age. Refractive astigmatism was stable in the age group from 18 to 50 years, while corneal astigmatism had a shift from with-the rule to against-the-rule with increasing age. Age, CCT, sphere, refractive astigmatism and corneal curvature (Km) were correlated with corneal astigmatism (standardized coefficients of are 0.006, p =0.011 for age, -0.001, p = 0.004 for CCT and −0.027, p <0.001 for sphere, 0.61, p <0.001 for RA, -0.05, p < 0.001 for corneal curvature). Conclusion: Refractive astigmatism is stable until the age of 50 years, while corneal astigmatism showed a shift from WTR to ATR with advancing age. Age, CCT, sphere, refractive astigmatism and corneal curvature(Km) were correlated with corneal astigmatism.